KETERCAPAIAN SEKOLAH BERASRAMA DALAM UPAYA PENINGKATAN MUTU DAN AKSES PENDIDIKAN - Perdana, Novrian Satria (EDUTECH, 2019)
One of the main problems in the field of education in Indonesia to date is quality and access. The decline in the results of the UN 2017 and APK to the next level indicates that a more comprehensive and affordable education model is needed. Dormitory education models in the form of boarding schools can implement a comprehensive-holistic education program including religion, academic development, the ability to survive (soft skills and hard skills), the insight of the Unitary Republic of Indonesia (NKRI), and building global insight. Considering the importance of boarding schools, up to now many boarding schools have been established but little research has been conducted on the conditions of their achievement based on the National Education Standards. Based on this, the purpose of this study was to analyze the achievement of boarding schools in an effort to improve access and quality of education seen from the National Education Standards (SNP). This research method uses purposive sampling by taking a sample in the Province of South Sumatra in 2017. The unit of analysis in this study is boarding schools in South Sumatra Province. Based on the achievement of boarding schools in South Sumatra Province, which consists of aspects of policy in the area about the existence of boarding schools, grades values of boarding schools, and collaboration with outside parties indicate that the existence of boarding schools can overcome the problems of access and quality of education in South Sumatra Province. Regarding access, students in remote areas have been provided with SMK Negeri 1 Gelumbang and for special access to athletes who need time and special curriculum, there is a Sriwijaya State Sports Middle School. To overcome the problem of efforts to improve the quality of education, there have been 17 Palembang State Senior High Schools and South Sumatra State High Schools which have educators and education personnel, learning and care curricula as well as very adequate facilities and infrastructure.Salah satu permasalahan utama dalam bidang pendidikan di Indonesia hingga saat ini adalah kualitas dan akses. Menurunnya hasil UN 2017 dan APK ke level selanjutnya menunjukkan bahwa diperlukan model pendidikan yang lebih komprehensif dan terjangkau. Model pendidikan asrama berupa pondok pesantren dapat melaksanakan program pendidikan holistik yang komprehensif meliputi agama, pengembangan akademik, kemampuan bertahan (soft skill dan hard skill), wawasan NKRI, dan membangun global wawasan. Mengingat pentingnya pondok pesantren, hingga saat ini sudah banyak didirikan pondok pesantren namun belum banyak dilakukan penelitian tentang kondisi pencapaiannya berdasarkan Standar Nasional Pendidikan. Berdasarkan hal tersebut, maka tujuan penelitian ini adalah untuk menganalisis capaian pondok pesantren dalam upaya peningkatan akses dan mutu pendidikan dilihat dari Standar Nasional Pendidikan (SNP). Metode penelitian ini menggunakan purposive sampling dengan mengambil sampel di Provinsi Sumatera Selatan tahun 2017. Unit analisis dalam penelitian ini adalah pondok pesantren yang ada di Provinsi Sumatera Selatan. Berdasarkan capaian pondok pesantren di Provinsi Sumatera Selatan yang terdiri dari aspek kebijakan di daerah tentang keberadaan pondok pesantren, nilai nilai pondok pesantren, dan kerjasama dengan pihak luar menunjukkan bahwa keberadaan pondok pesantren dapat mengatasi permasalahan tersebut. akses dan mutu pendidikan di Provinsi Sumatera Selatan. Soal akses, siswa di pelosok sudah disediakan SMK Negeri 1 Gelumbang dan untuk akses khusus atlet yang membutuhkan waktu dan kurikulum khusus ada SMP Olah Raga Negeri Sriwijaya. Untuk mengatasi masalah upaya peningkatan mutu pendidikan tersebut, telah terdapat 17 SMA Negeri Palembang dan SMA Negeri Sumatera Selatan yang memiliki pendidik dan tenaga kependidikan, kurikulum pembelajaran dan pengasuhan serta sarana dan prasarana yang sangat memadai.